Spatial dimensions of the effect of neighborhood disadvantage on delinquency - Vogel, Matt (Criminology, 2016)
Research examining the relationship between neighborhood socioeconomic disadvantage and adolescent offending typically examines only the influence of residential neighborhoods. This strategy may be problematic as 1) neighborhoods are rarely spatially independent of each other and 2) adolescents spend an appreciable portion of their time engaged in activities outside of their immediate neighborhood. Therefore, characteristics of neighborhoods outside of, but geographically proximate to, residential neighborhoods may affect adolescents’ propensity to engage in delinquent behavior. We append a spatially lagged, distance-weighted measure of socioeconomic disadvantage in “extralocal” neighborhoods to the individual records of respondents participating in the first two waves of the National Longitudinal Survey of Youth, 1997 Cohort (N = 6,491). Results from negative binomial regression analyses indicate that the level of socioeconomic disadvantage in extralocal neighborhoods is inversely associated with youth offending, as theories of relative deprivation, structured opportunity, and routine activities would predict, and that the magnitude of this effect rivals that of the level of disadvantage in youths’ own residential neighborhoods. Moreover, socioeconomic disadvantage in extralocal neighborhoods suppresses the criminogenic influence of socioeconomic disadvantage in youths’ own neighborhoods, revealing stronger effects of local neighborhood disadvantage than would otherwise be observed.